EVALUASI NILAI SEBELUM DAN SESUDAH PELATIHAN: APAKAH BISA MENANDAKAN KEBERHASILAN? - Sumarsono; Nur Muflihah; Minto; Sulung Rahmawan W.G, (Prosiding Seminar Nasional Sains, Teknologi, Ekonomi, Pendidikan dan Keagamaan (SAINSTEKNOPAK), 2021)
The success of the training lies in learning activities between the presenter and the participants. The role of technology media becomes substantial because it allows improving communication and transfer of knowledge. The main objective of workshop training is to introduce and practice statistical processing methods for research using IBM SPSS 23. The results of the training evaluation that a difference in the average value of participants' knowledge and abilities between pre-post conditions. A paired t-test was used and concluded that the average value after training was significantly higher than before. The training was conceptual into problem-based learning. It will increase its success with the support of application technology. So the choice of the appropriate application technology in training is substantial. The IBM SPSS 23 application was selected, with consideration of various sources. Finally, those activities have been carried out and accepted by the participants. In the future to add learning technology media (games, video tutorials) to the attractive tool and participant’s entertainment.